Implementasi Metode Period Order Qantity Dalam Pengendalian Persediaan Bahan Baku Crude Palm Oil - Michael Simanjuntak; Nerli Khairani (Lembaga Pengembangan Kinerja Dosen, 2023)
PKS Pagar Merbau is a plantation company engaged in palm oil processing. Due to the unpredictable level of demand, determining the timing and number of orders becomes difficult, resulting in increased inventory costs. By using the Period Order Quantity Method, it aims to be able to control Crude Palm Oil raw material inventory which will minimize inventory costs. The Period Order Quantity (POQ) method is a development of the Economic Order Quantity (EOQ) method where the number of orders can minimize the total cost of inventory. The results of applying this method, obtained the optimal number of orders of 1,208,798.12 kg for one order with a frequency of 101 times a year with a safety stock of 3,000,200.61 kg and a reorder point of 3,961,816.26 kg. The total inventory cost according to company policy is Rp. 3,159,298,770.65 while the total inventory cost according to the Period Order Quantity method is 2,879,961,532.42. Then the total inventory cost savings of Rp. 279,337,238.23 or 8.86%